Pengaruh Pengetahuan Investasi dan Kemajuan Teknologi Terhadap Keputusan Investasi di Kalangan Mahasiswa Gen-Z dengan Minat Investasi sebagai Variabel Intervening: Studi Kasus pada Mahasiswa Prodi Manajemen Universitas Negeri Makassar - Sahabuddin, Romansyah; Arif, Hery Maulana; Taufik, Finta Anindhita; Irfan, Muhammad Akram Zaki; Lestari, Wanda Ayu (Abadi Institute, 2024)
This research aims to analyze the influence of investment knowledge and technological progress on investment decisions of generation Z students, with investment interest as an intervening variable. Generation Z is a group born in the digital era and has broad access to investment information through technology. Investment knowledge and technological advances are expected to influence students' interest in investing, which in turn has an impact on their investment decisions. The method used in this research is path analysis with a sample of students from the Makassar State University Management Study Program. The research results show that investment knowledge and technological advances have a significant effect on investment decisions. Investment interest is proven to mediate the relationship between investment knowledge and technological progress and investment decisions. This research highlights the importance of financial literacy and the use of technology in supporting more effective investment decision making among students.